2008
DOI: 10.1167/iovs.07-0968
|View full text |Cite
|
Sign up to set email alerts
|

Laser Scanning In Vivo Confocal Microscopy Reveals Reduced Innervation and Reduction in Cell Density in All Layers of the Keratoconic Cornea

Abstract: Significant microstructural abnormalities were identified at every level of the keratoconic cornea and were related to disease severity. IVCM offers a potential insight into the pathophysiology of the microstructural changes in keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
99
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 34 publications
6
99
1
5
Order By: Relevance
“…The impairment of corneal innervation has been suggested to play a role in the pathogenesis of KC, and a significant reduction in NGF expression has been detected in KC corneas as part of an imbalance in the NGF signaling pathway [8,26]. Reduced numbers of stromal nerve fiber bundles together with an increase in tortuosity and nerve fiber diameter can explain the presence of prominent corneal nerves in KC [27]. To the best of our knowledge, tear NGF levels in patients with KC were measured for the first time in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The impairment of corneal innervation has been suggested to play a role in the pathogenesis of KC, and a significant reduction in NGF expression has been detected in KC corneas as part of an imbalance in the NGF signaling pathway [8,26]. Reduced numbers of stromal nerve fiber bundles together with an increase in tortuosity and nerve fiber diameter can explain the presence of prominent corneal nerves in KC [27]. To the best of our knowledge, tear NGF levels in patients with KC were measured for the first time in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo confocal microscope (IVCM) which provides cellular level resolution en face images of the cornea has also been commonly used in studying KC corneas. 12,13 Previous studies using IVCM have shown changes in the density of epithelial cells 13,14 and stromal keratocytes 14,15 in KC corneas. Increased haze/scatter in all the corneal layers 13,16 has also been observed in the KC eyes.…”
Section: Introductionmentioning
confidence: 96%
“…The physiology of nerve fibres tortuosity and its role in pathologies are not yet clear. Recent studies (e.g., [2,3]) are based on a manual qualitative assessment of corneal nerve tortuosity. Intra-observer and inter-observer variability can be high and unsuitable for an objective and reproducible evaluation [4,5].…”
Section: Introductionmentioning
confidence: 99%